Delayed and prolonged umbilical stump bleeding in a Caucasian newborn as a presenting feature of factor XIII deficiency. Issue 10 (7th October 2022) - Lim, David Boon Ngan; Mangles, Sarah; Goturu, Aruna
Abstract : A term Caucasian neonate with an uncomplicated birth history presented with persistent umbilical stump bleeding unresponsive to extensive topical haemostatic measures initially. He subsequently developed hypovolaemic shock. Routine full blood count and basic coagulation screen were unremarkable. He received packed red cell and cryoprecipitate transfusions. Further specialist coagulation studies performed revealed factor XIII deficiency. Genetic investigations demonstrated a compound heterozygosity for the disorder. He was later started on monthly prophylactic treatment of plasma-derived factor XIII. Clinicians should have a high index of suspicion for factor XIII deficiency for newborns with abnormal umbilical stump bleeding in the presence of no bleeding risk factors and normal routine blood investigations.